Typology and the Sacred Qur`ânic and Quasi Qur`ânic Narrative in Islamic Literature - El-Shamy, Hasan M. (Unisia, 2024)
This study explores the typological and sacred narrative traditions within Islamic literature, particularly focusing on Qur’anic and quasi-Qur’anic narratives. Using folkloristic methodologies, the research examines various folk genres, including fantasy, humorous, didactic, and belief narratives, and their structural components such as form, style, and content. The paper highlights how these narratives function within the broader social and cultural context of the Arab world, influencing worldview formation and socialization processes. Key analytical tools such as the tale-type and motif classification are employed to dissect narrative components, offering a deeper understanding of the interrelationship between religious texts and folk traditions. By analyzing these narrative forms, the study provides insights into how sacred narratives shape societal attitudes and behaviors, often embedding moral and religious lessons within everyday storytelling. The findings emphasize the enduring role of sacred texts in shaping collective identity and cultural expression, demonstrating the complex interplay between formal religious doctrine and popular narrative forms. This approach not only aids in understanding the transmission of cultural values but also reveals the adaptive nature of sacred narratives as they intersect with folk traditions across different historical and social contexts.